Smallholder farmers' willingness to pay for two-wheel tractor-based mechanisation services in Zambia and Zimbabwe - Ngoma, Hambulo; Marenya, Paswel Phiri; Tufa, Adane H.; Alene, Arega D.; Chipindu, Lovemore; Matin, Md Abdul; Thierfelder, Christian L.; Chikoye, David (Wiley, 2023)
Mechanisation is back among top development policy priorities for transforming African smallholder agriculture. Yet previous and ongoing efforts ubiquitously suffer from lack of scientific information on end-user effective demand for different types of mechanical innovations to inform public investment or business development programmes. We assess smallholder farmers' willingness to pay (WTP) for two-wheel tractor (2WT)-based ripping, direct seeding and transportation using a random sample of 2800 smallholder households in Zambia and Zimbabwe. Applying the Becker–DeGroot–Marschak Mechanism (BDM) experimental auctions, we find that at least 50% of sample households in Zambia and Zimbabwe were willing to pay more than the prevailing market prices for ripping. In nominal terms, sample households in Zimbabwe were willing to pay more than those in Zambia for the different services. Empirical results suggest that wealth is the strongest driver of WTP for tillage and seeding 2WT services while labour availability and using animal draft power reduce it. These findings imply a need to (i) raise awareness and create demand for 2WT-based services in an inclusive business manner that does not create perverse incentives and (ii) better target mechanisation to operations with comparative advantage, using approaches that bundle 2WT-based and other mechanisation services with asset-agnostic credit schemes or other interventions meant to overcome asset-mediated barriers.